Development Of An Enzymatic Deinking System Of Laser Printed Waste Papers - Lee , Chee Keong (2005)

(untitled)
Kaj ian ini memberi tumpuan kepada pembangunan proses penyahdakwatan enzimatik ke atas kertas terpakai. Dengan menggunakan kertas terpakai bercetak laser untuk penyahdakwatan enzimatik, pengoptimuman ke atas hidrolisis enzimatik dan penyingkiran ink dijalankan. Aktiviti optimum dan kestabilan terhadap pH dan suhu bagi selulase A " Amano" 3 (e), hemiselulase "Amano"90 (H) dan lipase F-AP 15 (L) dipilih untuk digunakan dalam proses penyahdakwatan. Suhu dan pH optimum bagi enzim e, H dan L adalah 55°e dan pH 2.5, 500e dan pH 4.5, 400e dan pH 7.5, masingmasing. The present work deal with the development of the enzymatic deinking process of waste papers. Based on the enzymatic deinking of laser-printed waste papers, studies on the optimization of enzymatic hydrolysis and ink removal were performed using commercial enzyme preparations. The optimum activities and stabilities at different pH and temperatures of the enzymes, cellulase A "Amano"3 (C), hemicellulase "Amano"90 (H) and lipase F-AP 15 (L) were selected for use in deinking process. The optimum temperature and pH of C, Hand L were 55°C and pH 2.5, 50°C and pH 4.5, 40°C and pH 7.5, respectively.